2020
DOI: 10.3390/foods9020110
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Unexpected Sphingolipids in Almonds and Pistachios with an Innovative Use of Triple Quadrupole Tandem Mass Spectrometry

Abstract: The densely packed storage of valuable nutrients (carbohydrates, lipids, proteins, micronutrients) in the endosperm of nuts and seeds makes the study of their complex composition a topic of great importance. Ceramides in the total lipid extract of some ground almonds and pistachios were searched with a systematic innovative discovery precursor ion scan in a triple quadrupole tandem mass spectrometry, where iso-energetic collision activated dissociation was performed. Five descriptors were used to search compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…On the basis of their molecular mass, these signals were associated to sphingolipids derivatized with oligosaccharide chains of different length. Recently, other authors reported the unexpected occurrence of sphingolipids in almonds and pistachios samples with intense signals at 714.6 m/z (GlcCer(t18:2/16:0)) and 698.6 m/z (GlcCer(d18:2/16:0)) 25 . In the pooled chocolate samples, an additional hydroxylation signal was observed at 730.9 m/z with a further mass increment of 16 m/z (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of their molecular mass, these signals were associated to sphingolipids derivatized with oligosaccharide chains of different length. Recently, other authors reported the unexpected occurrence of sphingolipids in almonds and pistachios samples with intense signals at 714.6 m/z (GlcCer(t18:2/16:0)) and 698.6 m/z (GlcCer(d18:2/16:0)) 25 . In the pooled chocolate samples, an additional hydroxylation signal was observed at 730.9 m/z with a further mass increment of 16 m/z (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This compound was proposed to be a plant sphingolipid, a member of the hydroxy sphingosine family. Sphingosine compounds were shown to take part in signalling pathways (Luttgeharm et al 2016) and the presence of such compounds was also confirmed in Prunus, i.e., almond kernels (Rubino et al 2020). The biosynthesis of plant sphingosine compounds includes the transportation of ceramide to Golgi apparatus, where ceramidases hydrolyse them to yield sphingosine and fatty acid.…”
Section: Discussionmentioning
confidence: 92%
“…This compound was proposed to be a plant sphingolipid, a member of the hydroxy sphingosine family. Sphingosine compounds were shown to take part in signalling pathways (Luttgeharm et al 2016 ) and the presence of such compounds was also confirmed in Prunus , i.e., almond kernels (Rubino et al 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Sphingolipids were not detected as markers of mild-heat pressed CPO in the crude fraction of palm oil, possibly due to the removal of neutral lipids and fatty acids through SPE of the polar lipid analysis. Rubino et al also reported that triglycerides could interfere with fragment ions of sphingosine ceramides, preventing the detection of sphingolipids . Despite the minute differences in lipid profiles between mild-heat and high-heat pressed CPO, the lipidomic analysis revealed that mild-heat pressed CPO contains 4–8 times higher levels of specific galactolipids and 3–4 times higher level of sphingolipids.…”
Section: Resultsmentioning
confidence: 99%